Teachers' Voice in Zambia: How to Make Them Involved in Curriculum Development - Jianhua Luo; Gift Muyunda (International Journal of Asian Education, 2021)
Curriculum Development in Zambia is highly centralized, with the Curriculum Development Center (CDC) being charged with developing the curriculum through consultative and participatory approaches through the course and subject panels where teachers are engaged. Nevertheless, there has been no empirical evidence to show how teachers are actively involved in the development process. This study aimed to investigate the phenomenon of teachers' involvement in the curriculum development process in Zambia. This study was qualitative and used a case study design approach. Data was collected using a semi-structured interview guide from secondary school teachers and headteachers. Raw data were collected through semi-structured interview forms from secondary school teachers and headteachers. The researcher analyzed the data using MAXQDA qualitative software to identify initial codes and generate emerging themes quickly. The results showed that secondary school teachers were dissatisfied with the present way of curriculum development, which insignificantly neglects them, and also, the majority of them have never participated in the development of the curriculum. Further, the results revealed that most of the secondary school teachers in Lusaka were willing to participate at any stage of the curriculum development in Zambia. This study concludes by arguing that secondary school teachers are significantly neglected to participate in the curriculum development in Zambia and recommends that the Ministry of General Education (MoGE) broaden the scope of secondary school teachers' participation in the curriculum developed through the Curriculum Development Center (CDC).